2018
DOI: 10.1080/19460171.2018.1451758
|View full text |Cite
|
Sign up to set email alerts
|

Established ideas from established institutions: austerity and structural reforms in the Finnish economic policy debate

Abstract: Instead of alternative economic ideas or institutional shifts, the post-financial crisis conjuncture has witnessed the persistence of neoliberal ideas and the strengthening of the institutions implementing them. Instructed by ideational institutionalism, this article analyzes the interplay between ideas and institutions by examining the public debate on economic policy in Finland during the euro crisis. We show how ideas formed by the dominant institutions of Finnish economic policy-making dominated the debate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The Competitiveness Pact, initially called the Social Pact, was largely framed by the 2008 economic crisis, which has had a lengthy aftermath. Research shows an unwillingness in Finnish media to provide alternative viewpoints to the narrative offered by hegemonic institutions, although there were conflicting views on the state of Finnish labour's competitiveness (Harjuniemi & Ampuja, 2019;Kaitila, 2019). While debate on austerity measures peaked in 2015, before the parliamentary elections (e.g.…”
Section: The Competitiveness Pact and The Obligatory Lawsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Competitiveness Pact, initially called the Social Pact, was largely framed by the 2008 economic crisis, which has had a lengthy aftermath. Research shows an unwillingness in Finnish media to provide alternative viewpoints to the narrative offered by hegemonic institutions, although there were conflicting views on the state of Finnish labour's competitiveness (Harjuniemi & Ampuja, 2019;Kaitila, 2019). While debate on austerity measures peaked in 2015, before the parliamentary elections (e.g.…”
Section: The Competitiveness Pact and The Obligatory Lawsmentioning
confidence: 99%
“…Since the crisis, the Finnish economy has struggled with stagnation and growing public debt, with no clear-cut solutions. Between 2008 and 2015, the Finnish government introduced various austerity measures, which did not greatly impact this progress (Harjuniemi & Ampuja, 2019). By 2015, when parliamentary elections were looming in Finland, the political discourse was filled with a sense of impending doom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When reporting on and analysing economic policy, journalists routinely turn to economic experts representing such institutions as banks, research institutes, government agencies, think tanks and labour market organisations (Harjuniemi and Ampuja 2019;Basu 2018;Chadwick et al 2020;Walsh 2020). The scholarship on journalistic representations of the financial crisis and the ensuing euro crisis has concluded that experts played a pivotal role in providing the public with justifications regarding such economic policy ideas as austerity (Berry 2019;Cawley 2016;Vaara 2014).…”
Section: Introductionmentioning
confidence: 99%
“…labour market reforms) as the only plausible way to deal with the economic predicament (Kay & Salter, 2014;Ojala & Harjuniemi, 2016;Tracy, 2012). Indeed, popular and mainstream media's one-sided approach has supported the establishment's narrative of necessary austerity (Basu, 2019;Harjuniemi & Ampuja, 2018;Power, Haynes & Devereux, 2016) and contributed to the legitimisation and 'strange nondeath' (Crouch, 2011) of neoliberal hegemony after the brief resurrection of alternative Keynesian ideas during the financial crisis of (see Blyth, 2013.…”
Section: Introductionmentioning
confidence: 99%